Experimental Study on Utilizing Polyethylene Terephthalate Waste as a Substitute for Coarse Aggregate in the Production of Lightweight Concrete - Yulius Rief Alkhaly; Yovi Chandra; Lis Ayu Widari (International Journal of Engineering, Science and Information Technology, 2023)
Concrete is a building material that consists of a mixture of aggregate and paste. Normal concrete has a unit weight of 2200 kg/m3 to 2500 kg/m3. In addition to normal concrete, lightweight concrete is also known which has a unit weight of less than 1900 kg/m3. The research was conducted to produce lightweight concrete by using aggregate from polyethylene terephthalate (PET) plastic waste as a substitute for coarse aggregate. This study used 40 cylindrical samples of 150 mm x 300 mm with variations in the use of PET aggregates of 25%, 50%, and 100% of the volume of coarse aggregate. The results show that the use of PET aggregates produces concrete with a decrease in compressive strength of 26%–39% and a decrease in water absorption of 2%–32% from normal concrete. Ultrasonic Pulse Velocity (UPV) testing showed that the concrete with PET aggregates had a lower wave propagation velocity compared to normal concrete. Moreover, Schmidt hammer and splitting tensile test showed that concrete with PET aggregates had lower rebound number and split tensile strength compared to normal concrete. PET substitution percentages of 25% and 50% resulted in unit weights of 2218 kg/m3 and 2102 kg/m3, respectively, which rule out the use of lightweight concrete. However, 100% PET substitution has a unit weight of 1855 kg/m3 with a compressive strength of 14.16 MPa, which can be categorized as moderate structural lightweight aggregate concrete.